World War II behind closed doors Stalin, the Nazis and the West - Rees, Laurence 1957- (BBC Books, 2008)
Examines the key decisions made by Stalin, Churchill and Roosevelt during the WWII. This book presents testimony obtained from nearly a hundred separate witnesses from the period. It features former Soviet secret policemen who talk frankly about their repressive work. It also features Allied seamen who reveal how they braved the Arctic convoys.